Penilaian dengan Metode Land Development Analysis (Studi Kasus Lahan di Kota Lubuklinggau, Sumatera Selatan) - Rio Jaka Tama; Rifki Khoirudin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
Research on vacant land in Lubuklinggau City uses Land Development Analysis (LDA) method and is done by using market approach and income approach to obtain land indication value per m². Furthermore, a city analysis that describes the economic conditions of Lubuklinggau City, a market analysis that describes the state of the property market. The type of this research is qualitative and quantitative by using primary data and secondary data. Primary data include income data, building expenditures and capital expenditures and others proposed as alternative uses, obtained by structured interviews and surveys. Secondary data were obtained from Lubuklinggau City Government, Central Bureau of Statistics, Bappeda and MAPPI. This assessment uses a market data approach and revenue approach to obtain Net Present Value (NPV), by simulating the property to be built Simple Housing property obtained NPV of Rp6.402.269.447. And land market value of Rp5,435,379,741. Both assessments were subsequently reconciled and resulted in a value of Rp5,946,800,000.